Blind Docking Analysis of Potential Drugs against SARS-COV-1 and SARS-COV-2 Proteins - Ferrari, Ivan Vito (International Journal of Scientific Research in Computer Science and Engineering, 2021)
In this short communication, more than 300 drugs were investigated by Blind Docking approach, by Autodock Vina Scoring Function with Pyrx Software. From Blind Docking Results, Deslanoside, Dactinomycin, Teicoplanin aglycone, Conivaptan, Paritaprevir, Acetyldigitoxin, Nafarelin, Lanatoside_C, Dydroergocristine, Dydroergotamine, Tirilazad, and Ubrogepant are potential candidates against SARS-COV-1 and SARS-COV-2 proteins. Particular attention, Acetyldigitoxin, Dactinomycin, and Deslanoside with Binding Energy about -12 .00 kcal mol -1 are higher binding Energies values against SARS-COV-2 Mpro. Regarding SARS-COV-2 RBD, Teicoplanin aglycone and Dactinomycin have a potentially significant role with a binding energy value of -12.50 kcal mol -1.